VALIDITY OF LELLI’S TEST IN DIAGNOSING ACUTE ACL INJURY AND ITS COMPARISON WITH THE OTHER CONVENTIONAL CLINICAL EXAMS - Usama, Muhammad; Ahmed Bajwa, Mubashar; Faheem , Muhammad Umer; Amin, Sara; Naveed, Muhammad; Ahmad Khan, Shaheryar; Sohail, Ayesha (Journal of Ayub Medical College Abbottabad, 2024)
Background: The anterior cruciate ligament (ACL) is a vital structure in the knee responsible for preventing anterior translation; and countering rotational and valgus stress. The anteromedial and posterolateral bundles of the ACL, which are distinguished by their attachments at the tibia and femur, respectively, make up the ACL. The study is designed to evaluate the diagnostic parameters of lever sign in acute settings when compared against MRI as investigation of choice and compare them with the conventional tests. Furthermore, effect of examination-under-anaesthesia and training level of the examiner on the diagnostic accuracy will be assessed. It was a prospective observational was performed. All the patients that presented to out-patient department of GTTH, Lahore from January to July 2023 and had a final diagnosis of ACL tear were included. Methods: Assessment was done by both undergraduates and postgraduates and those who underwent arthroscopy were placed in surgical cohort and arthroscopic findings were included in final analysis. Results: Eighty-three patients were assessed. Inferential analysis demonstrated that Lelli’s test had highest sensitivity (85.9%), NPV (64%) and diagnostic accuracy (85.5%). However, Lachman was most specific (94.7%) and had highest PPV (98.1). MRI itself is highly accurate (95.83%) when compared to arthroscopic findings. Though the results of each test when performed by postgraduates and under anaesthesia were significantly better; however, least difference was noted in case of Lelli test among awake and anesthetized and pre- and post-graduates’ exams. Conclusion: The Lelli’s test is highly sensitive and accurate when compared to the three conventional tests for ACL injuries. Furthermore, the manoeuvre and its interpretation are simple and reproducible; thus, can be used by highly trained healthcare professionals on awake patients with minimal discomfort. However, further research is needed to validate its biomechanics and role in partial ACL and multi-ligamentous injuries.